The pasture and forage industry in the Mediterranean bioclimates of Australia - Norman H.C.; Ewing M.A.; Loi A.; Nutt B.J.; Sandral G.A. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Farming systems in Mediterranean bioclimate areas of Australian rely heavily on pasture and forage legumes. This paper describes the farming systems in place, challenges to these systems and future directions for the development of new cultivars. Commercial production of seed, the export industry and the sources of funding for cultivar development are discussed.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)